Prevalence of Lactobacillus plantarum and Oenococcus oeni during spontaneous malolactic fermentation in Patagonian red wines revealed by polymerase chain reaction‐denaturing gradient gel electrophoresis with two targeted genes. (13th November 2014) - Valdés La Hens, D.; Bravo‐Ferrada, B.M.; Delfederico, L.; Caballero, A.C.; Semorile, L.C.
Abstract Background and Aims Information regarding the composition and dynamics of microbial communities throughout winemaking is always valuable to control the process and contributes to improving the quality of wine. The aims of this work were to analyse the diversity of lactic acid bacteria (LAB) species present during the spontaneous malolactic fermentation (MLF) of Patagonian red wines, and to isolate and identify native LAB species. Methods and Results Samples of Merlot and Pinot Noir wines were collected during three vintages at one commercial cellar. Through polymerase chain reaction (PCR)‐rpoB/denaturing gradient gel electrophoresis (DGGE), it was possible to identify 15 LAB species and through PCR‐16S rRNA V3 region/DGGE, 11 LAB species, during spontaneous MLF of these wines, mostly, Oenococcus oeni and Lactobacillus plantarum. These two species were also largely recovered by culture and analysed by the random amplified polymorphic DNA–PCR technique. Isolates of these two LAB species exhibited considerable genotypic heterogeneity. Conclusions The prevalence of O. oeni and Lb. plantarum in all samples suggests that both species are involved in leading the spontaneous MLF of these Patagonian wines. The analysis of the LAB microbiota in wine by PCR‐DGGE using two gene regions enabled addition to the number of species that can usually be detected during MLF. Significance of the Study The study offered a more complete knowledge of the LAB community present in wines in a cellar in the Argentine Patagonia during the spontaneous MLF. Our findings are particularly relevant, because they contribute to the possibility of designing an MLF starter composed of native strains of Lb. plantarum and O. oeni.